FROM CLASSROOM TO CURRICULUM: TEACHER PERSPECTIVES ON DEVELOPING A COE-BASED ENGLISH TEXTBOOK FOR VOCATIONAL HIGH SCHOOLS - Sisca Wulansari Saputri; Issy Yuliasri; Suwandi; Henrikus Joko Yulianto (English Review: Journal of English Education, 2025)
This study investigates teachers’ perspectives on developing Character of Excellence (CoE)-based English for Specific Purposes (ESP) textbooks within Indonesian vocational education. Grounded in the national Profil Pelajar Pancasila (PSP) framework, CoE aims to integrate employability skills with moral and ethical values in language learning. Using a qualitative descriptive approach, data were collected through semi-structured interviews with vocational English teachers and analyzed thematically. Findings reveal that while teachers understand the pedagogical and moral foundations of CoE, they face several challenges, including a lack of context-specific textbooks, limited ESP training, and minimal collaboration with industry. To overcome these challenges, teachers proposed five interconnected strategies emphasizing collaboration, authenticity, and innovation: (1) collaborative textbook development involving schools, industries, and curriculum experts; (2) project-based and simulation learning; (3) digital and multimedia integration; (4) professional development and peer mentoring; and (5) industry feedback mechanisms. These strategies collectively form a systemic reform model linking pedagogical quality, vocational relevance, and moral education. The study concludes that CoE-based textbook development is not merely a process of content adaptation but a transformative pedagogical movement that integrates linguistic competence, vocational expertise, and ethical values. By positioning English teaching as both a professional and character-building endeavor, the CoE-ESP model offers an innovative and globally relevant framework for value-based vocational English education.